Protective Effect of Coenzyme Q10 on Methamphetamine-Induced Apoptosis in Adult Male Rats - Gholipour, Fatemeh; Shams, Jamal; Zahiroddin, Alireza (Novelty in Biomedicine, 2017)
Background: The negative consequence of methamphetamine abuse is due to neuropathologic changes in the brain, which reduces dopaminergic neurons and result in damage to different brain areas. Neurotoxicity induced by methamphetamine increases the oxidative stress and associated with neuronal apoptosis. The role of the antioxidant coenzyme Q10 probably produces its neuroprotective effects. Therefore, the purpose of the present study was to examine the protective effect of coenzyme Q10 on methamphetamine-induced apoptosis in adult male rats. Materials and Methods: Fifty Wistar eight-week adult rats randomly divided into 5 groups: Healthy control, methamphetamine injection (Meth), methamphetamine injection and CoQ10 5mg/kg treatment (Meth+Post CoQ10 5mg/kg), methamphetamine injection and CoQ10 10mg/kg treatment (Meth+Post CoQ10 10mg/kg), methamphetamine injection and CoQ10 20mg/kg treatment (Meth+Post CoQ10 20mg/kg). Methamphetamine with a purity of 96% with a dosage of 20 mg/kg was injected Intraperitoneal. Coenzyme Q10 for three treatment groups was injected intraperitoneally for 14 days in a dosage of 5, 10 and 20 mg/kg/day. The protein expressions of Baxand Bcl2 were evaluated by western blotting technique. Results: Bax protein expression was significantly lower in Meth+Post CoQ10 5mg/kg (p=0.010) and so Meth+Post CoQ10 10mg/kg (p=0.004) comparing to Meth group. In addition, Bcl2 protein expression was significantly higher in Meth+Post CoQ10 5mg/kg comparing to Meth group (p=0.018). However, there were no significant differences between control and CoQ10 treatment groups. Bax/Bcl2 ratio was significantly lower in Meth+Post CoQ10 5mg/kg (p=0.005), Meth+Post CoQ10 10mg/kg (p=0.008) and Meth+Post CoQ10 20mg/kg (p=0.044) comparing to Meth group. Conclusion: We suggest that CoQ10 reduces the methamphetamine-induced apoptosis in the striatum of the rats through the reduction of apoptotic factors and increase of anti-apoptotic pathways.